MEMBANGUN BUDAYA MUTU DI MADRASAH UNGGUL (Studi Kasus di MAN 1 Jember dan MA Unggulan Nurul Islam Jember) - Siti Aminah Prayogo; Ari Widodo (STAI Ma'had Aly Al-Hikam Malang, 2019)
The quality culture is a strategy to improve upon the institution towards the needs of society and become a long term goal of Indonesian education. In Jember, there are Madrasah Aliya Negeri 1 Jember and Madrasah Aliyah Unggulan Nurul Islam Jember, both have specification in implementing Islamic education though they have different geographical location and users, but the indicators of quality culture can be seen in excellent programs of society based and students potential oriented, theyÂ also can maintain the achievement for local, national and international level. This research aims to reveal how to establish a quality culture in an excellent school. The aspects that will be concerned are a concept, value, culture and the implementation of quality culture in MAN 1 JEMBER and Madrasah Aliyah Unggulan Nurul Islam Jember. The writers will use the quaitative descriptive approach with repetition and continuity of analysis technique within collecting and analyzing data during the process of collecting data in the field and after the data gathered. From this research, it can be known that the quality culture concept of both schools used transformational leadership and intensive motivation is given. As for the quality culture of both school are different, MAN 1 Jember concerned about Ubudiyyah aspect and academic extracurricular program, while Madrasah Aliyah Unggulan Nurul Islamiyah concerned about literacy, discipline, and creative culture. To actualize these programs, the principal of both school, did the active communication intensively through all the school members anytime. In addition, the effect of this is all the school member always attempt to do the school program actively, and innovate the program to make a better institution.